Reaching Higher: Sacrifices and Brand Loyalty - Alafaleg, Nora (2024)
This thesis aims to develop the concept of brand sacrifice in brand loyalty theory to assess the extent to which brand sacrifice is a determining factor of brand loyalty relationships. In the wider theory of loyalty, sacrifice is seen as a key element, a higher and more extreme form of loyalty. When people are willing to make sacrifices, their relationships are more stable and enduring. However, customers' loyalty to brands is decreasing and becoming increasingly difficult to sustain. Thus, it is essential to examine acts of relationship maintenance, such as brand sacrifice, to develop sustainable brand loyalty. A literature review revealed that brand loyalty theories inadequately account for the element of brand sacrifice. Therefore, for the present research, in-depth, semi-structured interviews with open-ended questions were conducted with forty-four informants who are loyal to brands. The objectives were to develop the construct of brand sacrifice and investigate its significance in brand loyalty relationships and loyal consumers' motivations for engaging in brand sacrifice. Given that brand sacrifice has been overlooked in the literature, this thesis argues that brand sacrifice is one of the main components of brand loyalty and critically impacts its stability and longevity. While the literature has identified several obstacles to brand loyalty, this thesis posits that unwillingness to sacrifice is an obstacle to brand loyalty and prevents the development and maintenance of loyalty relationships. To foster strong loyalty relationships, this thesis develops a theoretical model of brand sacrifice motivations, classifying different goals and desires of making sacrifices in brand loyalty relationships. The novel findings revealed from the present study have several important implications on brand loyalty sustainability and the behaviours of loyal consumers form a brand sacrifice perspective.